PGPM-induced defense-related enzymes in aerobic rice against rice leaf blast caused by Pyricularia aryzae - Ng, Lee Chuen; Meon, Sariah; Sariam, O.; Othman, Radziah; Zainal Abidin, M. A. (Springer, 2016)
Rice blast caused by Pyricularia oryzae is the most devastative disease especially under aerobic cultivation systems. The bio-efficacy of plant growth-promoting microorganisms: Pseudomonas aeruginosa (UPMP1), Corynebacterium agropyri (UPMP7), Enterobacter gergoviae (UPMP9) and Bacillus amyloliquefaciens (UPMS3), Trichoderma harzianum (UPMT1) and Trichoderma virens (UPMT2) in induction of defense-related enzymes against Pyricularia oryzae was evaluated in rice cultivated under aerobic conditions. Under dual culture plate testing, all PGPMs indicated antagonism against P. oryzae with percentage inhibition radial growth (PIRG) which ranged from 51.69–81.97 %. The bio-efficacy of the respective PGPM in induction of defense-related enzymes in rice seedlings was evaluated based on individual inoculation before challenged inoculation with P. oryzae under greenhouse conditions. Inoculation of all PGPMs significantly reduced rice leaf blast severity at day eight after P. oryzae inoculation. The reduction in rice leaf blast disease severity was associated to the increase of peroxidase (PO), polyphenol oxidase (PPO) and phenylalanine ammonia-lyase (PAL) activities in rice seedlings when pre-inoculated with PGPMs. The highest leaf blast disease reduction (59.17 %) occurred with rice seedlings pre-inoculated with C. agropyri (UPMP9), followed by P. aeruginosa (UPMP1) (40.65 %), T. harzianum (UPMT1) (42.23 %), T. virens (UPMT2) (20.85 %), E. gergoviae (UPMP9) (17.84 %) and B. amyloliquefaciens (UPMS3). The high efficiency of PGPM in leaf blast disease suppression was associated with significant increase in total microbial activity (FDA hydrolysis) in rhizosphera soil (4.80–7.86 μg/g/0.5 h) compared to the control (2.25 μg/g/0.5 h). Thus, the application of PGPM is a potential alternative approach in rice leaf blast disease management of aerobic rice.